Motivasi Belajar Tokoh Utama Sangkakala Cinta Karya Khaeron Sirin Kajian Psikologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Di SMK - Nurmayati, Mala, Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2016)
Literature in shape needs to touch all human life. He not only covers the elements of civilization and culture, but all the elements that accompany the role of humans in the world as an agent in the civilization. In the majority of human life, is a form of literature that is essentially necessary requirement in leading to the taste of humans. Literature is one path to truth, in other fields who walked beside him as religion, philosophy, and science. Literary works bring people to an understanding of the values of life by engaging us to reveal the existence of this creator. Literature can communicate all that with God as creator. The main problem in this thesis is How Background sosiohistoris novelist Sirin Khaeron works Sangkakala Cinta?. How to build a structure that novel Sangkakala Cinta Khaeron Sirin work ?. How Aspect motivation to learn the key figures presented in the novel Sangkakala Cinta Sirin Khaeron work ?. How Implementation aspects of motivation to learn the main character in the novel Sangkakala Cinta Sirin Khaeron work as teaching materials in vocational literature? This study is the research literature, the research data gathering is done by collecting data from the literature. Researched the literature is not limited to books, but can also be documentary material, magazines, journals, newspapers and literary works, including novels. Data analysis techniques used in this research is to use the model of semiotic readings. The results of this thesis can be described as follows: Background sosiohistoris novelist Sangkakala Cinta works Khaeron Sirin is a society in social inequality to be conveyed that there is still no way to deal with obstacles in achieving a desirable ideals. Aspects of motivation to learn the key figures presented in the novel Sangkakala Cinta works Khaeron Sirin, the main characters of Fakih implied a lot about patience, persistence, determination, unity, obedience, and everything about aspects of life. Implementation aspects of motivation to learn the main character in the novel Sangkakala Cinta Sirin Khaeron work as teaching materials in vocational literature is their educational value in Novel Sangkakala Cinta Khoeron Sirin's work, it is appropriate to be used and implemented in the instructional literature.